Sosialisasi Cyber Ethics Dalam Membangun Budaya Literasi Digital di SMK Bina Harapan - Titik Rahmawati; Eka Yulia Sari; Agung Priyanto; Anjasmara Tanjung Sakti; Fredimus Kasang (Indonesian Journal Publisher, 2024)
The current development of information technology has led to digital interactions which are often known as cyberspace. Cyberspace is a notional environment where communication via computer networks occurs, in this case via the Internet, which can be in the form of text, images, audio, video, animation or anything in digital form. The virtual world now has almost the same intensity as the real world. With recent technological advances making it possible to have more intensity than the real world in the future. This has created new problems in social life, especially among teenagers who are the biggest users of cyberspace. Many bad things happen in teenagers' interactions in cyberspace, such as cyber bullying, or accessing content that is not suitable for teenagers to consume. This certainly cannot be allowed. To be able to overcome this problem, the outreach team carried out cyber ethics outreach activities in building a digital literacy culture. The aim of this service activity is to help increase understanding of cyber ethics among SMK Bina Harapan students. The number of participants in the socialization was 63 students consisting of class X and class XI of SMK Bina Harapan. From this activity, an evaluation was carried out in the form of a post-test using a multiple choice questionnaire via Google Form. The questions are written in essay form consisting of two answers Yes or No. The results of the Google Form questionnaire show that 90% of Bina Harapan Vocational School students understand the cyber ethics socialization material. Thus, it can be concluded that after conducting socialization, it can help increase students' understanding of Bina Harapan Vocational School about the importance of cyber ethics in building a digital literacy culture, so that their digital literacy activities become safer and healthier.